The addition of natural clay and industrial and agricultural waste on the performance of green and sustainable concrete - Inzimam Ul Haq; Ayub Elahi; Atif Khan; Afsar Ali; Qadir Bux alias Imran Latif Qureshi; Aïssa Rezzoug; Mohd Aamir Mumtaz (Scientific Reports)
Abstract Cement production is a major contributor to global CO2 emissions, necessitating the development of sustainable alternatives such as fiber-reinforced concrete incorporating supplementary cementing materials (SCMs) and agricultural waste. This approach keeps the environment safe by reducing the consumption of conventional raw materials for concrete production. Incorporating the SCMs in concrete can potentially improve the mechanical and durability properties. This research evaluated the behavior of concrete mixtures using different proportions of natural wheat straw fiber, bentonite, and silica fume (SF). The fresh property was investigated by using a workability test, and mechanical properties were investigated by using compressive strength and split tensile strength. Bulk density, water absorption, and sorptivity tests were also performed to investigate the durability of concrete. Scanning electron microscopy (SEM) was conducted to evaluate the microstructure and morphology of the developed concrete mixtures. The results revealed that the slump value decreased with incorporating SCMs and fibers (83–42 mm). The compressive strength ranged from 11 MPa to 23 MPa, increasing with the increased Bentonite and SF dosages. Splitting tensile strength ranged from 2.2 MPa to 2.7 MPa, showing an increase with increased dosages of SCMs and fibers. The addition of WSFR compromised the compressive strengths of the developed mixtures, however, the ductility of the mixtures was improved with the incorporation of the WSFR. The SEM confirmed the CSH gel formation in the mixtures containing bentonite and SF. This gel formation improved the mechanical properties of the concrete, reduced water absorption, and increased its resistance to acid. The resulting concrete mixtures can address the carbon emissions associated with cement production and provide a sustainable construction material.